Temperature abuse and Salmonella Typhimurium colonization disrupt the indigenous bacterial communities of pasteurized bovine milk over time - Greeshma Bharathan; Balamurugan Sadaiappan; Bismi Phasaludheen; Dema Alneyadi; Sunil Mundra; Shabarinath Srikumar (Scientific Reports)
Abstract Even though the population structure of the bovine milk residential bacterial population is known, the alterations in the population structure associated with food safety issues, such as temperature abuse/pathogen colonization, are unknown. Here, alterations of the bacterial population, either incubated at 37 °C (temperature abuse) or inoculated with Salmonella Typhimurium (pathogen colonization), were characterized using full-length 16S rRNA sequencing. At zero hour, the bacterial population of milk primarily constituted of Firmicutes and Thermi. Of the 218 genera identified, Thermus (37%) and Streptococcus (34%) were the most dominant. The 12-h incubation at 37 °C replaced almost 96% of the population by Firmicutes, exemplified by a remarkable increase in the abundance of the genus Bacillus. Concurrently, only 36 genera survived, with an abundance of Bacillus, which showed a 98-fold increase during the 12-h incubation. Similarly, only 150 genera remained after 12 h in Salmonella-inoculated milk. Both temperature abuse and Salmonella inoculation significantly reduce bacterial diversity and richness. Nonmetric multidimensional scaling analysis between the control and Salmonella inoculated samples was significantly distinct at all times, confirming alterations in the bacterial population during Salmonella colonization. Even though the load of Firmicutes increased temporally, bacteria belonging to the genera Bacillus, Macrococcus, and Serratia genera were depleted in Salmonella inoculated milk samples. Taken together, both experimental conditions, viz. temperature abuse and Salmonella contamination, demonstrated a significant drop in residential milk bacterial diversity. This general drop in bacterial diversity could allow Salmonella to occupy and colonize the milk matrix.